DETERMINANTS OF SATISFACTORY HEALTH SERVICES IN THE CITY OF TSHWANE - Worku, Zeleke (International Journal of Psychosocial Rehabilitation, 2020)
Residents of the City of Tshwane require satisfactory health care services from health professionals working in health facilities. The study has identified three key predictors of satisfactory health services. The aim of study was to determine predictors of adequate health service delivery in public health facilities. The research was motivated by perceived lack of adherence to the integrated development plan (IDP) that was developed for ensuring an optimal provision of basic health care services to residents of the City of Tshwane. As part of the study, information was gatthered from 420 households. Factor analysis was used for identifying key predictors of health service delivery. Diagnostic procedures showed that all fitted models were theoretically reliable. About 65% of households were happy with the quality of health care services provided to residents. Findings of the study indicate that substantial adherence to the integrated development plan (IDP) of the City is helpful for enhancing the quality of basic health service delivery in the City of Tshwane.